Evolution of HR Analytics in India - a Detailed Analysis - Raj, Rashmi; Lalhall, Alka; Raj, Shilpi (Journal of Economics and Management, 2024)
The technological domains and trends of artificial intelligence (AI), robotics, business intelligence, big data and analytics, edge computing, hyper automation, Block chain, Democratization, Human Augmentation, and Multi experience are enabling mankind to innovate and create superhuman capabilities. This leaves human resources (HR) to fight the battle of replacing people-literate technology with people-literate people. With the developing trends, the propensity for analytics and intricate algorithms created a breakthrough into a creative zone that extended a manageable workforce. The purpose of this study is to review the earlier studies conducted based on evolution and emergence of HR analytics. It tries to investigate through prior works done on business analytics, big data, business intelligence and on HR Analytics a swell as literature concerning innovation and adoption of various models, tools and techniques.